Pengaruh absorptive capacity, innovation capabilities dan implementasi open innovation terhadap kinerja UKM di Yogyakarta - Hendy Kurnia Putra; Arif Hartono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effects of absorptive capacity, innovation capabilities, and open innovation on SME performance in the Special Region of Yogyakarta. Previous research on open innovation in the Indonesian context has been conducted, yet it needed more specificity and omitted certain variables concerning the enhancement of SME performance. Therefore, this study aims to address this gap. A total of 202 respondents contributed to this research. Data were analyzed using SPSS and PLS-SEM with SmartPLS software. The findings reveal that absorptive capacity, innovation capabilities, and open innovation variables positively influence SME performance. This study contributes to enriching the literature on the concept of open innovation and SME performance. Furthermore, it offers valuable insights for business practitioners to implement these three variables for the enhancement of their business performance.